Exploring barriers and facilitators of vaginal birth after caesarean section (VBAC), awareness, and preferences among females in Western Saudi Arabia - Daniyah Aloufi; Omar Saggaf; Zainab Ali Alkhalifah; Hassan Alalawi; Nadia Alhazmi (Journal of Family Medicine and Primary Care)
Background: Women with a history of previous Cesarean Sections (CS) are faced with two choices during their pregnancy: Vaginal Birth After Cesarean (VBAC) or Elective Repeat Cesarean Delivery (ERCD). VBAC refers to vaginal delivery in women who have previously undergone a CS. Objectives: Despite limited studies on VBAC in Saudi Arabia, this research aims to assess the knowledge and awareness of Saudi women regarding VBAC. Methodology: This cross-sectional study was conducted among adult females in Western Saudi Arabia utilizing a convenient snowball sampling technique. The total number of participants was 901 females. The participants completed a self-administered questionnaire, which covered general information, knowledge about VBAC, and factors influencing their decision. Statistical analysis employed Chi-squared, Independent T-Test, and ANOVA. Results: Our findings revealed that 67.5% of participants had inadequate knowledge about VBAC. Only 45.6% of participants were familiar with the term VBAC. The primary reason for choosing CS over VBAC was medical necessity, as reported by 36.3% of participants. The most common reasons for rejecting VBAC were fear for their child’s safety and the fact that a CS was recommended, both reported by 35.1%. The lowest reported reason was external interference from family or spouses, at 10.5%. Conclusion: Although the majority of our sample consisted of highly educated women, most exhibited poor knowledge regarding VBAC. Therefore, raising awareness about VBAC, especially through healthcare professionals and their clinics, is essential.